Dynamic expression of cytokine and transcription factor genes during experimental Fasciola gigantica infection in buffaloes - Shi, Wei; Wei, Zhi-Yong; Elsheikha, Hany M.; Zhang, Fu-Kai; Sheng, Zhao-An; Lu, Ke-Jing; Wang, Dong-Ying; Huang, Wei-Yi; Zhu, Xing-Quan (BioMed Central, 2017)
Background